An exploration of the impact of oracy intervention on the quality of Key Stage Four students’ classroom talk and students’ confidence levels when talking in the classroom - Hawksworth, S (2023)
This research explores the impact of oracy intervention sessions during one weekly session of tutor-time on the quality of Key Stage Four students’ classroom talk and students’ confidence levels when talking in the classroom. Through this mixed-methods study, a system for oracy intervention is trialled for five months and reflected upon, to be refined for the next academic school year. Using Mercer’s (1995) four categories of classroom talk, with exploratory talk being the end goal in this study, the findings of this study appear to evidence that a blend of teacher-led and student-led pre-planned oracy interventions can improve the quality of students’ exploratory talk, namely: their utterance length; turn taking skills; listening skills and reduce their use of disputational language. The findings also conclude that student confidence levels can be improved through oracy interventions, highlighting the social benefits of teaching oracy, which may enhance curriculum engagement and academic attainment overall.